2018
DOI: 10.3390/nu10070858
|View full text |Cite
|
Sign up to set email alerts
|

β-glucan Salecan Improves Exercise Performance and Displays Anti-Fatigue Effects through Regulating Energy Metabolism and Oxidative Stress in Mice

Abstract: Fatigue induced by prolonged exercise not only leads to the decrease of exercise capacity, but also might be the cause of many diseases. In consideration of the side effects of pharmacological drugs, dietary supplements seem to be a better choice to ameliorate exercise-induced fatigue. The present study aimed to investigate the anti-fatigue effect of Salecan, a novel water-soluble β-glucan, during exercise and explore the underlying mechanisms. Male Institute of Cancer Research (ICR) mice were divided into fiv… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

3
39
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 52 publications
(42 citation statements)
references
References 38 publications
(61 reference statements)
3
39
0
Order By: Relevance
“…The weight-loaded forced swimming test is the most commonly used animal model to evaluate the extent of fatigue [3]. A longer swimming time indicates the increase of exercise capacity and reduced susceptibility to fatigue [20,21]. As shown in Figure 1, in comparison with the vehicle group (323.40 ± 107.99), the swimming time of mice in in all three WOPs groups was longer (WOPs-LG: 511.65 ± 107.58; WOPs-MG: 556.33 ± 104.13; WOPs-HG: 657.53 ± 130.90) and the difference was statistically significant ( p < 0.01).…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…The weight-loaded forced swimming test is the most commonly used animal model to evaluate the extent of fatigue [3]. A longer swimming time indicates the increase of exercise capacity and reduced susceptibility to fatigue [20,21]. As shown in Figure 1, in comparison with the vehicle group (323.40 ± 107.99), the swimming time of mice in in all three WOPs groups was longer (WOPs-LG: 511.65 ± 107.58; WOPs-MG: 556.33 ± 104.13; WOPs-HG: 657.53 ± 130.90) and the difference was statistically significant ( p < 0.01).…”
Section: Resultsmentioning
confidence: 99%
“…Several blood biochemical indicators were used to evaluate the degree of muscle fatigue and to explore the underlying mechanism, such as lactate dehydrogenase (LDH), blood urea nitrogen (BUN), creatine kinase (CK) and blood glucose [3,20]. In the present study, we examined whether WOPs could cause positive effects on these related biochemical parameters in the serum sample of mice (Figure 2).…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…In our clinical trial, we found significant anti-inflammatory effects of glucan supplementation in cancer-related fatigue [39]. In addition, numerous studies published lately showed that glucan improved exercise performance [40], improved syndromes of chronic fatigue syndrome via improved levels of GSH and SOD in the brain [41] and enhanced the endurance capacity while improving the fatigue-related recovery [41,42]. The possible mechanisms suggested by these studies are improvements in oxidation and regulation of energy metabolism by glucan.…”
Section: Discussionmentioning
confidence: 72%
“…Several biochemical parameters were used to evaluate the extent of muscle fatigue and muscle damage, including BUN, LDH, and CK. [ 31–33 ] The concentration of LDH and CK were significantly increased in SR mice compared with mice in CON group, while PTE treatment remarkably reduced them both (Figure 2B,C). The level of BUN increased significantly in SR mice, but there was no significant difference between mice of SR group and SR+PTE group (Figure 2D).…”
Section: Resultsmentioning
confidence: 95%